The Effect of Church Conflict on the Growth of Pentecostal Churches in Kenya: A Case Study of Selected Churches in Nairobi - John Miatu Thiga; Gyang D. Pam; James Nkansah-Obrempong (European Scientific Journal, ESJ, 2021)
The purpose of the study was to determine the effect of church conflict on the growth of Pentecostal churches in Kenya with focus on selected churches in Nairobi which are struggling with growth. The objectives of the study were to investigate the nature of conflicts in the Pentecostal churches in Kenya, determine the effect of conflict on the growth of Pentecostal churches in Kenya, and to assess the conflict resolution mechanisms employed to solve the conflict in Pentecostal churches in Kenya. The study was carried out in branches of four churches which experienced growth challenges, namely: Full Gospel Churches of Kenya, Kenya Assemblies of God, Pentecostal Evangelism Fellowship of Africa, and Worldwide Gospel Church of Kenya. The study used qualitative research approach as it intended to collect data based on participants’ subjective experience, and its ability to uncover unexpected and exploring new avenues. The target population was church leaders who have been in the church for at least two years. The study used purposive sampling method to select the church leaders in influential positions (i.e., leaders that direct and/or lead a church ministry) of the selected churches according to the church leadership structure espoused by each of the four selected churches. Proportionate stratified sampling was used where equal number of units was selected from each stratum. Data was collected using face-to-face individual interview schedule. The data was analyzed thematically using content analysis method. The researcher came up with the vital themes, recurring ideas, and patterns of belief, which assisted with the integration of the results. The study found that there were conflicts in all the churches under study. The study established that there were top leadership wrangles at the national level seeking to control the church. There were also local church leadership wrangles pitting pastors and other leaders and conflict among other leaders within the church. The study established that conflict negatively affected the growth of the church as the churches lost members to other churches around. Among the conflict resolution mechanism used were prayer and fasting, dialogues, and courts. The study recommends that the Pentecostal churches should adopt conflict resolution methods and avoid conflicts by practicing inclusivity.